Perfil de uso de plantas medicinais e fitoterápicos para manejo de sintomas por pacientes com doenças reumatológicas no hospital universitário João de Barros Barreto - FREITAS, Ana Rosa Sales de (2023)
Introduction: Medicinal plants have great potential for use by patients with rheumatological diseases. These patients, in general, may regularly present physical disability, lower productivity and quality of life, and often seek complementary alternative therapies. Therefore, it’s important to carry out studies that seek to know the socio-demographic profile and the use of medicinal plants by these patients. Methodology: This is a cross-sectional observational study, in which the data were obtained by applying a questionnaire to 100 patients in the waiti ng room of the Rheumatology outpatient clinic. The answers provided by the patients were evaluated and organized using the Microsoft Office Excel 2016 program. Results: Among the 100 patients interviewed, 84% were women, 53% of those interviewed were over 59 years old and 74% responded that they lived in Belém. The use of medicinal plants was reported by 76% of patients. When asked about their opinions on medicinal plants, 60% responded that they believed that plants “because they are natural, they are not harmful” and 69% responded that they can “help conventional treatment”. In addition, 74% said they did not inform the doctor about the use of medicinal plants and 85.5% said they did not inform themselves with health professionals before starting to consume them. Discussion: Most respondents were women, over 59 years old and residing in Belém, which can be attributed to the demographic profile of rheumatological diseases, which affects more women and older ages. In addition, 85.5% of the individuals interviewed said they did not get information from any health professional, which is worrying as the elderly are more vulnerable to drug interactions due to polypharmacy. Conclusion: It is concluded that a considerable percentage of patients routinely consume medicinal plant-based products, especially patients over 50 years of age, with low education and in order to improve the symptoms of rheumatological diseases, such as pain. Thus, it is essential to invest in research with medicines derived from plants, to prove or discard their benefit, in addition to showing the population the correct way to use these medicines.